Experiencescape Sebagai Pemicu Revisit Intention Pada Kafe-Kafe Baru di Jawa Timur - Sienatra, Krismi; Rizky Firmansyah , Muhammad Agung; Asepta, Uki Yonda (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
New cafes have the challenge of keeping visitors coming back. The return of visitors is a form of the cafe's acceptance of visitors. By using the S-O-R Stimulus, Organism, Response framework in the form of an experiencescape measured by hospitality components, social components, sensory components, and functional components to influence revisit intention. The sample for this research was 251 visitors who came at least once to 4 new cafes (less than 3 months) in 2 cities in East Java. Using multiple linear regression analysis shows that the hospitality component, social component, sensory component and functional component have a significant effect on revisit intention. These results show that new cafes must emphasize an impressive experiencescape for visitors so that it will generate revisit intention.